Protective and pathological roles of tissue factor in the heart - Bode, M. F.; Mackman, N. (Hämostaseologie, 2015)
Tissue factor (TF) is expressed in the heart where it is required for haemostasis. High levels of TF are also expressed in atherosclerotic plaques and likely contribute to atherothrombosis after plaque rupture. Indeed, risk factors for atherothrombosis, such as diabetes, hypercholesterolaemia, smoking and hypertension, are associated with increased TF expression in circulating monocytes, microparticles and plasma. Several therapies that reduce atherothrombosis, such as statins, ACE inhibitors, beta-blockers and anti-platelet drugs, are associated with reduced TF expression. In addition to its haemostatic and pro-thrombotic functions, the TF : FVIIa complex and downstream coagulation proteases activate cells by cleavage of protease-activated receptors (PARs). In mice, deficiencies in either PAR-1 or PAR-2 reduce cardiac remodelling and heart failure after ischaemia-reperfusion injury. This suggests that inhibition of coagulation proteases and PARs may be protective in heart attack patients. In contrast, the TF/thrombin/ PAR-1 pathway is beneficial in a mouse model of Coxsackievirus B3-induced viral myocarditis. We found that stimulation of PAR-1 increases the innate immune response by enhancing TLR3-dependent IFN-_ expression. Therefore, inhibition of the TF/thrombin/PAR-1 pathway in patients with viral myocarditis could have detrimental effects. Conclusion: The TF : FVIIa complex has both protective and pathological roles in the heart.
Keywords: Tissue factor; haemostasis; atherothrombosis; cardiac remodelling